Der Beschluss als Rechtsgeschäft - Skauradszun, Dominik (Das Bürgerliche Recht. Habilitationen, 2020)
»Resolutions as Legal Transactions« Notwithstanding a great need for resolutions as legal instruments of collective bodies in making decisions, a general codified resolution framework does not exist in Germany. Due to the similar legal situation in France, Poland, Austria, Switzerland, and the Netherlands, this study develops a harmonising legal doctrine of resolutions in collective bodies such as supervisory boards, shareholders' and creditors' meetings and presents its 43 theses in German and English.